Reactive or transgenic increase in microglial TYROBP reveals a TREM2‐independent TYROBP–APOE link in wild‐type and Alzheimer's‐related mice. Issue 2 (12th December 2020) - Audrain, Mickael; Haure‐Mirande, Jean‐Vianney; Mleczko, Justyna; Wang, Minghui; Griffin, Jennifer K.; St George‐Hyslop, Peter H.; Fraser, Paul; Zhang, Bin; Gandy, Sam; Ehrlich, Michelle E.
Abstract: Introduction: Microglial TYROBP (DAP12) is a network hub and driver in sporadic late‐onset Alzheimer's disease (AD). TYROBP is a cytoplasmic adaptor for TREM2 and other receptors, but little is known about its roles and actions in AD. Herein, we demonstrate that endogenous Tyrobp transcription is specifically increased in recruited microglia. Methods: Using a novel transgenic mouse overexpressing TYROBP in microglia, we observed a decrease of the amyloid burden and an increase of TAU phosphorylation stoichiometry when crossed with APP/PSEN1 or MAPT P301S mice, respectively. Characterization of these mice revealed Tyrobp ‐related modulation of apolipoprotein E ( Apoe ) transcription. We also showed that Tyrobp and Apoe mRNAs were increased in Trem2 ‐null microglia recruited around either amyloid beta deposits or a cortical stab injury. Conversely, microglial Apoe transcription was dramatically diminished when Tyrobp was absent. Conclusions: Our results provide evidence that TYROBP‐APOE signaling does not require TREM2 and could be an initiating step in establishment of the d isease‐a ssociated m icroglia (DAM) phenotype.